2018
DOI: 10.1142/s2424835518500030
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computed Tomography in Determining the Occurrence of Dorsal and Intra-articular Screw Penetration in Volar Locking Plate Osteosynthesis of Distal Radius Fracture

Abstract: This study demonstrated a high incidence of dorsal and intra-articular screw penetration detected by CT scan which was not apparent in plain radiograph. We recommend that surgeons adhere to the principle of only near cortex fixation and downsizing the locking screw length by 2 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, for dorsal intraarticular fractures, reducing screw length may lead to gap formation or intraarticular steps due to insufficient engagement of the dorsal cortex 3,23 . Interestingly, dorsal protruded screws are not always related to extensor tendon rupture 21,24 . Sugun et al 12 found that screw protrusion of more than 1.5 mm in the third or fourth dorsal compartment is likely to cause problems, including ultrasonographic tenosynovitis and ultrasonographical partial or total tendon rupture with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for dorsal intraarticular fractures, reducing screw length may lead to gap formation or intraarticular steps due to insufficient engagement of the dorsal cortex 3,23 . Interestingly, dorsal protruded screws are not always related to extensor tendon rupture 21,24 . Sugun et al 12 found that screw protrusion of more than 1.5 mm in the third or fourth dorsal compartment is likely to cause problems, including ultrasonographic tenosynovitis and ultrasonographical partial or total tendon rupture with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, distal locking screws for volar plating in distal radius fracture that are intentionally 2-4 mm shorter than the measured length have been suggested due to the high incidence of dorsal screw penetration detected by CT. 18,21 A biomechanical study suggested that unicortical locking screws should be at least 75% of the measured length of a bicortical screw that provides stiffness similar to that of bicortical fixation in extraarticular distal radius fractures. 22 However, for dorsal intraarticular fractures, reducing screw length may lead to gap formation or intraarticular steps due to insufficient engagement of the dorsal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of screw length has been reported in several studies. In a retrospective study evaluating screw length after repair of distal radial fractures in humans using postoperative radiographs and CT scans, all screws appeared appropriately sized on radiographs but, when analyzed using CT scans, 63% of screws were excessively long and 17% of those were intraarticular 14 . In an ex vivo study of human phalanges, screws were considered optimal in length in only 49.2% of instances.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 22 reported that distal screw insertion close to the articular surface and dorsal rim may be effective in maintaining anatomical reduction; the authors advocated double-tiered subchondral support fixation. Diong et al 23 reported that CT revealed a high incidence of dorsal screw penetration that was not evident on plain radiography, but reported no tendon rupture. They recommended unicortical screw insertion near the cortex, while describing that bicortical fixation may be desirable in osteoporotic patients with displaced dorsal fragments.…”
Section: Discussionmentioning
confidence: 99%